A Note on Plato, Symp. 223b-d - Maria Broggiato (Myrtia, 2025)
This paper argues that in the final section of Plato’s Symposium (223b-d) we can recognize a deliberate reference to some lines belonging to an elegy of the corpus Theognideum (Theogn. 467-472). This elegy has often been attributed by modern scholars to Evenus of Paros, the sophist and poet who was in contact with Socrates and his circle.